FEATURES OF MICROBIAL COLONIZATION IN THE INTESTINES IN COLIC IN INFANTS WITH A HISTORY OF ANTIBIOTIC THERAPY - О. Моштук; М. Кісельова (Bukovynian State Medical University, 2024)
Research on the problem of colic in infants shows inconsistencies in conclusions regarding its etiology, pathogenesis, diagnosis, and management. They suggest that colic remains a hot topic for further research. Experimental evidence does not support the claim that colic is a self-limiting and safe process. On the contrary, the described possible consequences of the eff ects of colic on the behavior and quality of the disturbed digestion indicate that this is an understudied phenomenon. The aim of the study: to evaluate the comparative relationship between qualitative microbial colonization and the state of digestive processes in the intestine and the development of colic in infants aged 2 weeks to 6 months who were treated with antibiotics from birth to 5 months of age, taking into account the clinical severity of colic manifestations, by studying the comparative characteristics of clinical and demographic indicators and qualitative results of bacteriological examination of feces.  Research materials and methods. The study included 103 infants with colic diagnosed according to Rome IV criteria, aged 2 weeks to 6 months, mean age 2 months, with a history of antibiotic treatment. The main group consisted of infants with severe colic (n=43), and the comparison group consisted of infants with mild clinical manifestations of colic (n=34). The peculiarities of the microbial colonization of the intestine and the functional state of digestion were determined on the basis of the results of the study of the colic coprogram. To achieve this goal, we performed macroscopic and microscopic examination of feces, assessment of clinical and anamnestic indicators: obstetric history, gestational age, sex, anthropometric data, history of diseases, nosologic characteristics of diseases and treatment received by infants. The materials of the publication concerning examination, laboratory and scientifi c research and treatment of patients comply with the norms of bioethics, as confi rmed by the conclusion of the Bioethics Commission of the Lviv National Medical University named after Danylo Halytskyi (Protocol No. 1 dated January 25, 2021). The materials of the publication regarding the observance of ethical, moral and legal principles while performing the work correspond to the norms of bioethics, as evidenced by the conclusion of the Bioethics Commission of the Lviv National Medical University named after Danylo Halytskyi (Protocol No. 3 dated 18.03.2024). Informed written consent was obtained from the parents of the patients before the start of the study, explaining the purpose, tasks, and methods of the laboratory research. Statistical analysis was performed using descriptive and analytical statistics. In connection with the non- Gaussian distribution of the obtained data (testing with the Shapiro- Wilks test), the mean values were presented as median with 1 and 3 quartiles (Me [25 %; 75 %]). Their comparison between the studied groups was performed using the Mann- Whitney (U) test. Percentages are presented as fractions with the mean arithmetic error (Р±mр, %). To compare frequencies in groups, Fisher's exact test (F) was used for small samples and Pearson's test (X 2) for larger samples. The Tau- Kendall test was used to evaluate the correlation of non-parametric and rank characteristics. p<0.05 was considered as the minimum value of reliability of all obtained data. The complex of researches was carried out within the framework of the planned topics of research work of the Department of Pediatrics and Neonatology of the FPDO of Lviv National Medical University (LNMU) named after Danyla Halytskoho: «Study of the infl uence of ecological- social and micro- ecosocial factors on the development of a pathological condition in children by improving the methods of early diagnosis, treatment and prevention» (2019-2023, state registration number: 0114U000108).  Results. The results of our microbiological examination of the feces are consistent with the fact that the imbalance of the microbial «landscape» of the intestine is the probable source of the formation of an excessive amount of gases in it and the bright clinical manifestation of colic in infants with a history of antibiotic therapy. Babies with a severe clinical course of colic compared to babies who had a mild course of colic were distinguished by the severity of colic manifestations by the duration of periods of «causeless» crying (hours): in the main group, more than half of children (55.81±7.57 %) had 3 degrees of severity and more than a third (37.21±7.37 %) - 2 degrees, while in the comparison group all children (100 %) had 1 degree of severity of the condition (p<0.001). Bifi dobacteria, lactobacilli, and Escherichia coli were signifi cantly decreased in the feces of children with severe colic, which in turn led to a signifi cant activation of opportunistic enterobacteria and enterococci, and with the presence in the coprogram of iodophilic bacteria indicated that colic is a type of functional indigestion, fermentative dyspepsia, especially in infants aged 2 weeks to 6 months who had a history of antibiotic therapy. There was a signifi cant diff erence between the indicators of coprogram in children of the studied groups, namely the reaction of feces in infants was acidic, p<0.001. Of the total number of subjects, children of the main group (81.40 %) had neutral fat in stool samples, fatty acids were detected (67.44 %), p<0.001. The presence of iodophilic fl ora was observed in children of the main group 88.37 compared to 61.76 %, (p=0.008), soaps were present in 88.37 % in the main group and 26.47 % in the comparison group (p<0.001) and mucus 83.72 % in the main group and 0 in the comparison group, p<0.001. These data indicate diff erences in digestive processes, changes in the composition of the microbiota and digestive insuffi ciency in the small intestine, which precede fermentative dyspepsia. The results of our research added to the evidence that pathological microbial colonization and functional disturbances of digestive processes in all parts of the intestine contribute to the strengthening of fermentation processes in the large intestine and are a probable cause of excessive formation of intestinal gases in infants and the manifestation of colic. Further studies on the study of the pathogenetic mechanisms of colic and the determination of the causal relationship between etiological factors and the brightness of clinical manifestations of colic, taking into account the eff ect of antibiotic therapy in the fi rst 5 months of life on the intestinal microbiome, will allow to develop eff ective strategies for prevention and treatment of colic in infants. Conclusions. 1. The results of our microbiological examination of feces are consistent with the fact that the imbalance of the microbial «landscape» of the intestine is the probable source of the formation of an excessive amount of gases in it and the bright clinical manifestation of colic in infants with a history of antibiotic therapy. 2. Babies with severe clinical course of colic, compared with babies who had a mild course of colic, diff ered in the severity of colic manifestations according to the duration of periods of «causeless» crying (hours): in the main group, more than half of children (55.81±7.57 %) had the 3rd degree of severity and more than a third (37.21±7.37 %) had the 2nd degree, while in the comparison group, all children (100 %) had the 1st degree of severity of the condition (p<0.001). 3. Bifi dobacteria, lactobacilli, and Escherichia coli were signifi cantly decreased in fecal bacteriology of children with severe colic, which in turn caused signifi cant activation of opportunistic enterobacteria and enterococci. 4. There was a signifi cant diff erence between the indicators of the coprogram in children of the studied groups, namely the reaction of feces in infants was acidic. Of the total number of subjects studied, the main group had neutral fat in stool samples, detected fatty acids, and the presence of iodophilic fl ora, soap and mucus. These data indicate diff erences in digestive processes, changes in the composition of the microbiota, and insuffi ciency of digestion in the small intestine, which precedes fermentative dyspepsia.